Phages adapt to recognize an O-antigen polysaccharide site by mutating the “backup” tail protein ORF59, enabling reinfection of phage-resistant Klebsiella pneumoniae - Ping Li; Wenjie Ma; Jun Cheng; Cuixing Zhan; Hongzhou Lu; Jiayin Shen; Xin Zhou (Emerging Microbes and Infections)
Phages demonstrate remarkable promise as antimicrobial agents against antibiotic-resistant bacteria. However, the emergence of phage-resistant strains poses challenges to their effective application. In this paper, we presented the isolation of a phage adaptive mutant that demonstrated enhanced and sustained antibacterial efficacy through the co-evolution of Klebsiella pneumoniae (K. pneumoniae) 111-2 and phage ZX1Δint in vitro. Our experiments revealed that phage ZX1Δint successfully completed the adsorption phase by binding to the host surface, specifically targeting the capsular polysaccharide (CPS) receptor via the primary receptor-binding protein (RBP) ORF60 and the auxiliary RBP ORF59. Upon exposure to phage predation, mutations in genes wbaP, wbaZ or wzc, which encode the synthesis of the CPS, conferred resistance by reducing phage adsorption. In response to these host defense mechanisms, the adaptive mutant phages have evolved to utilize an alternative binding site located on an O-antigen site of lipopolysaccharide (LPS) through a mutation in the backup RBP ORF59. This evolutionary change enabled the phages to reinfect previously phage-resistant strains. Notably, the adaptive mutant phage PR2 carrying the ORF59 mutation Q777R, demonstrated the capacity to infect both wild-type and resistant strains, exhibiting prolonged antimicrobial activity against the wild strains. In conclusion, our findings elucidated a complex phage-host adsorption-antagonism mechanism characterized by mutation-driven alterations in phage receptor recognition. This work contributes to a deeper understanding of phage adaptability and highlights the potential for phages to combat phage-resistant bacteria through an in vitro evolutionary approach.